2020
DOI: 10.1111/jcpe.13289
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal regeneration versus extraction and dental implant or prosthetic replacement of teeth severely compromised by attachment loss to the apex: A randomized controlled clinical trial reporting 10‐year outcomes, survival analysis and mean cumulative cost of recurrence

Abstract: Periodontal regeneration versus extraction and dental implant or prosthetic replacement of teeth severely compromised by attachment loss to the apex: A randomized controlled clinical trial reporting 10-year outcomes, survival analysis and mean cumulative cost of recurrence Abstract Background: Periodontal regeneration can change tooth prognosis and represents an alternative to extraction in teeth compromised by severe intra-bony defects. The aim of this study was to compare periodontal regeneration (PR) with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
89
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(96 citation statements)
references
References 25 publications
4
89
2
1
Order By: Relevance
“…The emphasis on “3‐wall” bony defects was due to their higher chances of successful regeneration (Weinberg & Eskow, 2000). Recent developments in periodontal regenerative techniques and materials have pushed the boundaries of what is considered “regenerable” (P. Cortellini et al, 2020). Papapanou & Tonetti differentiated osseous defects into “suprabony” defects, “infrabony” and “interradicular or furcation” defects (Papapanou & Tonetti, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The emphasis on “3‐wall” bony defects was due to their higher chances of successful regeneration (Weinberg & Eskow, 2000). Recent developments in periodontal regenerative techniques and materials have pushed the boundaries of what is considered “regenerable” (P. Cortellini et al, 2020). Papapanou & Tonetti differentiated osseous defects into “suprabony” defects, “infrabony” and “interradicular or furcation” defects (Papapanou & Tonetti, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…2,6,4 This tendency could be explained by the shift towards preserving the natural dentition over placing dental implants, and the popularity of regenerative therapies. 18,19 It has been shown that the health of the periodontium next to a retained hopeless tooth can be maintained by surgical intervention with frequent maintenance care. 20,21 Even for molars with Class II to III furcation involvement, a recent study 22 reported that these molars could still respond well to periodontal therapy, and every effort should be made to maintain these teeth whenever possible.…”
Section: Discussionmentioning
confidence: 99%
“…Costs were determined by the actual costs of the necessary procedures derived from guide-price by the local government in Shanghai (see Table S1 for detail). Calculations of mean cumulative costs (MCCs) were performed as described (Cortellini et al, 2020;Shi et al, 2020).…”
Section: Costsfortreatmentandmanagementof Complicationsmentioning
confidence: 99%